Japanese folktales for language learners = Mukashibanashi de manabu nihongo - Sato, Eriko 1962-; Sato, Anna (Tuttle Publishing, 2022)
"Learn about Japanese culture while improving your language skills! Japanese Folktales for Language Learners presents 22 traditional stories in parallel Japanese and English versions on facing pages, with detailed notes and exercises aimed at beginning to intermediate learners. This book can be used as a language reader and will be of great interest to anyone wishing to learn more about Japanese culture and folklore. The stories in this collection gradually increase in length and complexity as the book progresses. They include: "The Candy-Buying Ghost" - A female ghost mysteriously buys candy every night from a small village shop, until one night she reveals her true identity and her tragic story. "The Old Man Who Made Trees Blossom" - Regarded as one of the five greatest Japanese folktales, this touching story tells of a kind old man who uses his magical powers for good. "The Abandoned Mother" - An elderly woman is abandoned at the top of a mountain by her own son, a reference to the old practice of senicide in Japan. Vocabulary lists, cultural notes, exercises and discussion questions help to reinforce an understanding of the stories and bolster language skills. Free online recordings of all the stories are provided"--Publisher's description.